Avoid overstepping the bounds of evidence: the role of the orthodontist in managing pediatric Obstructive Sleep Apnea - Rinchuse, Daniel J.; Boggio, Andrea; Manni, Antonio; Cozzani, Mauro (Frontiers in Oral Health, 2024)
IntroductionPediatric Obstructive Sleep Apnea (OSA) is a common sleep-related breathing disorder often linked to distinct craniofacial features and malocclusions. While orthodontic treatments, particularly maxillary expansion and mandibular advancement, have been suggested for managing this condition, the results remain controversial and are based on low-quality evidence. This paper aims to summarize the ongoing debates on this topic by reviewing relevant literature and highlighting the role of the orthodontist in diagnosing and managing OSA in daily clinical practice.Discussion and conclusionsAccording to the present review, there is insufficient evidence to either confirm or deny the effectiveness of oral appliances for treating pediatric OSA due to significant methodological limitations, such as small sample sizes, inadequate control groups, short study durations, and a lack of long-term follow-up. Additionally, this condition cannot be diagnosed solely based on craniofacial morphology, but an interdisciplinary evaluation is strictly required. In addition, orthopedic treatment may be considered only as an adjunct therapy for children with craniofacial anomalies increasing the risk for OSA, and the combination of multiple therapeutic approaches may be necessary to achieve effective treatment outcomes.